2018
DOI: 10.33021/jenv.v3i1.396
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Sludge as an Alternative Energy Resource: A Review

Abstract: <p align="justify">In recent years, concerns regarding to wastewater sludge disposal have increased globally. Production of sludge has increased recently due to the growth of population. Wastewater sludge classified as a hazardous substance, it is not easy to dispose because of certain treatment is required. Typically, sludge is treated at secured landfill which its limited in availability and expensive. On the other hand, wastewater sludge originated from biological treatment contains organic substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Especially regarding the wastewater sludge which needs to be disposed properly. (Kurniawan, Hakiki & Sidjabat, 2018)…”
Section: Discussionmentioning
confidence: 99%
“…Especially regarding the wastewater sludge which needs to be disposed properly. (Kurniawan, Hakiki & Sidjabat, 2018)…”
Section: Discussionmentioning
confidence: 99%
“…Using anaerobic digestion to provide energy from both types of wastewater sludge can obtain low-cost fuels compared with natural gas (Vatachi, 2019). (Kurniawan et al, 2018) According to Mills et al (2014), the United Kingdom water industry generates about 800 GWhpa of electrical energy from the sewage sludge. Traditionally energy recovery from sewage sludge features anaerobic digestion with biogas utilization in combined both heat and power systems.…”
Section: Sludge To Energymentioning
confidence: 99%
“…Furthermore, the essential area for under drain sand bed area was 5,100 m 2 . content, it can be used as a potential energy source for future if it is properly used (Kurniawan et al, 2018). It is also observed that anaerobic digestion is preferable, for variety of sludge wastewater, but this method is limited in general (Vatachi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While for the scenario in Figure 2, material transported to the landfill in a form of the fix-carbon residue from gasifier unit and liquid tar residue from gas-liquid separator unit. The amount of this residue less than the amount of dry (Kurniawan, Hakiki, and Sidjabat, 2018) In addition, green energy produced from the gasification process can also be used as an alternative energy source (McNamara et al, 2016;Ji et al, 2010). CO2 being an important constituent in our atmosphere, the changes of concentration in our atmosphere can affect the global climate (Sun et al, 2015;Anderson, Hawkins, and Jones, 2016;Kusrini et al, 2017;Zhang, Zhao, and Xu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 (a) The industrial wastewater; (b) Mechanical separation of solid particles from wastewater; (c) Dried sludge; (d) The existing flow of wastewater treatment and sludge handling (Kurniawan, Hakiki, and Sidjabat, 2018). …”
mentioning
confidence: 99%